A clinician's guide to statistics and epidemiology in mental health: Measuring truth and uncertainty - Ghaemi, S Nassir (Cambridge University, 2013)
Describes statistical concepts in plain English with minimal mathematical content, giving an insight into which statistics to believe - and why.